2015
DOI: 10.1111/jcpe.12413
|View full text |Cite
|
Sign up to set email alerts
|

Deproteinized bovine bone in association with guided tissue regeneration or enamel matrix derivatives procedures in aggressive periodontitis patients: a 1‐year retrospective study

Abstract: Surgical treatment of AgP patients by either GTR or by application of EMD/DBX yielded similarly successful clinical results at 1-year post-treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 73 publications
1
16
0
Order By: Relevance
“…In non‐randomized, comparative studies, the reported outcomes did not show a significant advantage of one surgical approach over another; the differences between groups were not significantly different. In both included RCT, no significant advantage of guided tissue regeneration procedures over EMD and simplified papilla preservation flap (SPPF) approaches could be found …”
Section: Resultsmentioning
confidence: 96%
“…In non‐randomized, comparative studies, the reported outcomes did not show a significant advantage of one surgical approach over another; the differences between groups were not significantly different. In both included RCT, no significant advantage of guided tissue regeneration procedures over EMD and simplified papilla preservation flap (SPPF) approaches could be found …”
Section: Resultsmentioning
confidence: 96%
“…Allograft was added to the EMD to provide mechanical support for the soft tissue during the healing phase. 13 Stability of regenerative outcomes is expected after 1-year follow-up, as a similar study reported stability of CAL and PD and comparable results between 6 months and 1 year of regenerative treatment in patients with AgP. 8 Specifically, Rakmanee et al 8 reported 1.6-and 1.7-mm gain in CAL at 6 and 12 months, respectively, after GTR treatment in patients with AgP.…”
Section: Discussionmentioning
confidence: 89%
“…They reported similar clinical results in terms of PD reduction and CAL over 1 year of study. 13 Studies comparing GTR and EMD did not find significant differences in the clinical outcomes of two treatment modalities. 6,14 However, most studies did not take into account the different intrabony configurations as a variable factor in the interpretation of outcomes.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations